Keputusan Pembelian Kartu Prabayar Telkomsel Dilihat dari Kualitas Produk dan Harga Kompetitif : (Studi Kasus pada Pelanggan Kartu Prabayar Telkomsel di Kelurahan Ulak Karang Selatan Padang) - Pingki Wahyuni; Febsri Susanti (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This study aims to prove the relationship between the influence of product quality and competitive price on the purchasing decisions of Telkomsel prepaid cards. In this study, the number of samples was 87 respondents. The data was collected using a questionnaire and the sampling technique was carried out by purposive sampling technique, namely sampling based on the criteria set by the researcher. The data analysis technique used is multiple regression analysis and to test the hypothesis using statistical t test. The results showed that: 1) Product quality has a significant effect on purchasing decisions for Telkomsel prepaid cards in Ulak Karang Selatan Village, Padang. Product quality has a significance value of 0.000, the significant value is smaller than alpha 0.05. 2) Competitive prices have a significant effect on purchasing decisions for Telkomsel prepaid cards in Ulak Karang Selatan Village, Padang. Competitive prices have a significance value of 0.000, the significant value is smaller than an alpha of 0.05.